Analisis Penerimaan Learning Management System Berbasis Problem Based Learning Menggunakan Technology Acceptance Model - Divita Aulia Listyaningsih; Yeni Anistyasari (CV. SINAR HOWUHOWU, 2026)
The use of the Learning Management System (LMS) in learning is growing as an effort to support the delivery of materials, learning activities, and evaluations in an integrated manner. The existence of an LMS allows the learning process to take place more flexibly and encourages student involvement in learning activities. However, the success of an LMS implementation is determined not only by the quality of the system developed, but also by the level of user acceptance of the technology. This study aims to analyze the acceptance of Learning Management System based on Problem Based Learning using the Technology Acceptance Model (TAM). The study used a quantitative approach with a survey method involving 35 students of class X TKJ SMKN 3 Buduran as respondents. Data was collected through a questionnaire compiled based on five TAM constructs, namely Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), Behavioral Intention (BI), and Actual Use (AU). Data analysis was carried out descriptively using average values and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis using SmartPLS 4. The results showed that all TAM constructs obtained an average score in the high category with a range of 3,479–3,733. In addition, the results of the PLS-SEM analysis showed that all relationships between constructs had a positive and significant influence with a p-value of < 0.05. The findings show that LMS based on Problem Based Learning is well received by students, so that the Technology Acceptance Model is able to explain user acceptance of LMS in supporting informatics learning.